Metabolic-associated fatty liver disease and autoimmune hepatitis: an overlooked interaction. (3rd October 2021) - Gaber, Yasmine; AbdAllah, Mohamed; Salama, Asmaa; Sayed, Manar; Abdel Alem, Shereen; Nafady, Shaymaa
ABSTRACT: Introduction: Metabolic-associated fatty liver disease (MAFLD) is the most common liver disease globally, and affects about a quarter of the general population. Autoimmune hepatitis (AIH) is a severe (sometimes fatal) liver disease that affects children and adults, with a rising prevalence. Thus, not surprisingly, both conditions can frequently coexist, with potential synergistic impact on the course of the disease and response to therapy of both entities. Areas covered: In this work, the authors aimed to provide a narrative updated review on this interaction, diagnosis, and management of MAFLD/AIH and the current challenges. Expert opinion: Clarifying the nature of the complex interaction between the two diseases was hampered by a myriad of factors, particularly the previous diagnosis of exclusion for fatty liver disease associated with metabolic dysfunction. The recent redefinition of fatty liver disease that led to the development of positive diagnostic criteria for MAFLD has the premise to help in circumventing some of these challenges.